Notai vescovili, notai chierici, notai con duplice nomina nella chiesa ascolana del XIII secolo - Cameli, Martina (Scrineum, 2013)
The study aims at conducting research into the strict relationship between the notaries and the bishops of Ascoli Piceno, at marking some aspects of town notaries and, finally, at examining some undeniable peculiarities of a “border” Church, geographically and politically collocated between the State of Church (Patrimonium Beati Petri) and the Kingdom of Sicily, and constantly wavering between the obedience to the Apostolic See and a natural inclination towards the pars Imperii. By the examination of the data that may be deduced from notarial subscriptions and from the registration of the daily activities carried out by the bishops for administration of the diocese, it is possible to point out a rich notarial world, where, besides the notaries designated by the bishops themselves, we can find other notaries who declare a double appointment, often both imperial and ecclesiastical (of the bishop, of the pope, of pontifical legates or of the Marca rectores), but also only ecclesiastical (i.e. two nominations coming from ecclesiastical authorities). Then, we can isolate very interesting moments and instances about documentary procedures of the Church of Ascoli and the role of the notaries: first of all, the ‘favour’ given by the bishops, in spite of their uncommon potestas faciendi notarios, to the imperial notaries for the writing of documents concerning with the bishops themselves, but also the meaning of the work furnished by the notaries in order to rule the diocese. The result is that, besides to give a strong guarantee for the bishops’ power in patrimonial and institutional matters and an effective rationalization in management of the documentary resources, the notaries have tried to support the exigency and the will of the bishops to differentiate – to the panorama of contemporary documentation – their own charters, thus making products which appear intermediate between notarial and chancellery style, rich of solutions that should be able to communicate the image of the power they came from.